A novel formulation of Folic acid gel in the treatment of Desquamative Gingivitis - Khan, Saif; Rahman, Syed Ziaur (Bangladesh Journal of Medical Science, 2020)
Abstract not available Bangladesh Journal of Medical Science Vol.19(2) 2020 p.187-188